Cardiovascular biochemical risk factors among women with spontaneous preterm delivery. Issue 2 (21st January 2018) - Heida, Karst Y.; Kampman, Marlies A.; Franx, Arie; De Laat, Monique W.; Mulder, Barbara J.; Van der Post, Joris A.; Bilardo, Catia M.; Pieper, Petronella G.; Sollie, Krystyna M.; Sieswerda, Gertjan T.; Ris‐Stalpers, Carrie; Oudijk, Martijn A.
Abstract: Objective: To determine whether women delivering preterm have unfavorable cardiovascular profiles as compared with women who deliver at term. Methods: A prospective observational cohort study enrolled 165 women with spontaneous preterm delivery (sPTD) at 24 +0 and 36 +6 gestational weeks in three perinatal care centers in The Netherlands between August 2012 and August 2014. Total cholesterol, triglycerides, high‐density lipoprotein (HDL)‐cholesterol, low‐density lipoprotein (LDL)‐cholesterol, apolipoprotein, glucose, and homocysteine were measured within 24 hours after delivery. Lipids and cardiovascular biochemical risk factors were compared between women with sPTD and an external comparison group of 30 women with term delivery via analysis of covariance. Results: Mean gestational age at delivery was 30.7 ± 3.6 weeks in the sPTD group and 40.3 ± 1.3 weeks in the reference group. Data were adjusted for body mass index, age, and center. As compared with the reference group, total cholesterol and LDL‐cholesterol levels were lower and glucose levels were higher among women with sPTD. Conclusion: An association between sPTD and unfavorable lipids and cardiovascular biochemical risk factors was not established. The higher levels of glucose in the sPTD group might be due to increased insulin resistance, which is associated with a higher risk of sPTD. Abstract : Postpartum women with spontaneous preterm delivery had lower levels of total cholesterol and higher levels of non‐fasting glucose relative to women who delivered at term.